4CPS-221 Impact of hospital-city communication based on the multiprofessional and collaborative development of the discharge letter on the continuity of patients' medication management-city study. (March 2019) - Geneletti, L; Chanoine, S; Lugosi, M; Allenet, B; Bouilet, L; Bedouch, P; Deroux, A
Abstract : Background: Hospitalisation leads to changes in the patient's medication management. Currently, hospital-city communication, based mainly on the hospitalisation report, does not allow an efficient transmission of information to ensure early and optimal post-hospital care of patients. A discharge letter was imposed at the regulatory level to improve the continuity of patients' medication management after discharge from hospital. However, explanations for drug changes remain limited. Purpose: The objective of this study was to evaluate the impact of the collaborative multiprofessional implementation, integrating the clinical pharmacist, of the discharge letter explaining all drug regimen changes, and its transmission to the general practitioner by secure messaging, would improve continuity of care medication of the patient. Material and methods: A prospective randomised controlled cluster study was performed in two care units of the internal medicine department of a university hospital centre between September 2017 and February 2018. The impact of the discharge letter was evaluated based on the average number of drug changes performed in hospital and continued by general practitioners, in each group, 3 months after discharge. A sensitivity analysis was conducted on the justification of the non-continuation of drug changes by the general practitioners, based on international STOPP and START criteria. The number of re-hospitalisations was compared between the two groups and the satisfaction of general practitioners concerning this approach was evaluated by questionnaire. Results: A total of 189 patients were included in the analyses: 92 in the interventional group and 97 in the control group. The mean number of discontinued drug changes after discharge did not differ significantly between the two groups (1.5±1.5 vs. 1.7±1.6, p=0.35). Sensitivity analysis showed similar results. A downward trend in rehospitalisations 3 months after hospitalisation was highlighted in the interventional group (22% vs. 31%, p=0.15). General practitioners were satisfied by this approach (91%, n=111). Conclusion: Transmission to the general practitioner of the discharge letter, explanation of all drug regimen changes and elaborated collaboratively and multiprofessionally, seems to be a promising tool. A large multicentre prospective study should be conducted to confirm these findings. References and/or acknowledgements: No conflict of interest.